2020
DOI: 10.3390/computation8030064
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Autonomous Agents’ Decisions in Learning to Cross a Cellular Automaton-Based Highway via Artificial Neural Networks

Abstract: A lot of effort has been devoted to mathematical modelling and simulation of complex systems for a better understanding of their dynamics and control. Modelling and analysis of computer simulations outcomes are also important aspects of studying the behaviour of complex systems. It often involves the use of both traditional and modern statistical approaches, including multiple linear regression, generalized linear model and non-linear regression models such as artificial neural networks. In this work, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Early stopping was frequently used in training the models, the optimal model stopped training after 3000 epochs as the validation loss started to slightly increase (Figure 3). In this work, the Algorithm was adapted to a multilayer neural network to calculate the Connection Weights Product (CWP) as recently suggested by multiple studies [24,25]. More specifically, this study adapted the algorithm to a two hidden layer network as demonstrated by Where 𝐶𝑊𝑃 𝑥,𝑧 is the connection weight product of an input metric to a class output , 𝑤 𝑥𝑛 is the weight connecting an input metric to a first hidden layer neuron 𝑛, 𝑣 𝑛𝑚 is the weight connecting a first hidden layer neuron 𝑛 to a second hidden layer neuron 𝑚, and 𝑞 𝑚𝑧 is the weight connecting a second hidden neuron 𝑚 to an output .…”
Section: Machine Learning Model Developmentmentioning
confidence: 99%
“…Early stopping was frequently used in training the models, the optimal model stopped training after 3000 epochs as the validation loss started to slightly increase (Figure 3). In this work, the Algorithm was adapted to a multilayer neural network to calculate the Connection Weights Product (CWP) as recently suggested by multiple studies [24,25]. More specifically, this study adapted the algorithm to a two hidden layer network as demonstrated by Where 𝐶𝑊𝑃 𝑥,𝑧 is the connection weight product of an input metric to a class output , 𝑤 𝑥𝑛 is the weight connecting an input metric to a first hidden layer neuron 𝑛, 𝑣 𝑛𝑚 is the weight connecting a first hidden layer neuron 𝑛 to a second hidden layer neuron 𝑚, and 𝑞 𝑚𝑧 is the weight connecting a second hidden neuron 𝑚 to an output .…”
Section: Machine Learning Model Developmentmentioning
confidence: 99%